3D printing process of oxidized nanocellulose and gelatin scaffold. Issue 12 (13th August 2018) - Xu, Xiaodong; Zhou, Jiping; Jiang, Yani; Zhang, Qi; Shi, Hongcan; Liu, Dongfang
Abstract: For tissue engineering applications tissue scaffolds need to have a porous structure to meet the needs of cell proliferation/differentiation, vascularisation and sufficient mechanical strength for the specific tissue. Here we report the results of a study of the 3D printing process for composite materials based on oxidized nanocellulose and gelatin, that was optimised through measuring rheological properties of different batches of materials after different crosslinking times, simulation of the pneumatic extrusion process and 3D scaffolds fabrication with Solidworks Flow Simulation, observation of its porous structure by SEM, measurement of pressure-pull performance, and experiments aimed at finding out the vitro cytotoxicity and cell morphology. The materials printed are highly porous scaffolds with good mechanical properties.